STRATEGI GURU DALAM MENINGKATKAN MAHARAH AL-QIRA’AH SISWA KELAS IX MADRASAH TSANAWIYAH NURUL HIKMAH HAURGEULIS - Zaytunil Hikmah; Dewi Utami; Dadan Mardani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This aim of this research is to determine the problem of maharah al-qira'ah of class IX students and teachers' strategies in improving the maharah al-qira'ah of students IX class of Madrasah Tsanawiyah Nurul Hikmah Haurgeulis in 2023. This research use desciptive qualitative approach. The data collection process was through the maharah al-qira'ah test for students IX class, classroom observations during learning, interviews with students and teachers as well as madrasah heads to obtain information and documentation. The result of this research indicate that students problems in maharah al-qira'ah are caused by linguistic and non-linguistic problems. Linguistic problems include aspects of sound and writing. And non-linguistic problems include student intelligence and motivation. The teacher's strategy for improving the maharah al- qira'ah of class IX Madrasah Tsanawiyah Nurul Hikmah Haurgeulis students in 2023 is to use the practice method and the sentence method. In delivering the material the teacher uses an expository strategy and in enriching the students' vocabulary the teacher uses the mufrodat strategy. Keywords: Teacher Strategy, Maharah Al-Qira'ah, Arabic Language Problems